Meaning of Happiness Based on ERG Theory in Middle-Aged Korean Women - Hee Jin Shin; Jeung Im Kim (Korean Society of Women Health Nursing, 2019)
PURPOSE: The purpose of this study was to explore the components and nature of happiness in middle-aged women in Korea. METHODS: Thirty middle-aged women living in metropolitan Seoul and Gyeonggi and Chungcheong provinces agreed to participate in this study. The data were collected through in-depth interviews with the participants in one-on-one settings. The data were analyzed qualitative using Colaizzi's method of phenomenology. RESULTS: The three theme clusters were extracted from the raw data, along with 13 themes and 138 meaningful sentences and phrases. The three happiness theme clusters in middle-aged women were "live healthy for stability," "rule one's mind for harmony," and "activate hopes for self-esteem." The first theme cluster included healthy life, economic stability, physical youth, and positive thought. The second theme cluster included that harmonious family, ruling of mind, my position as invisible person in social relationships, and precious relationships to support. The last theme included the center of one's life is oneself, a sense of accomplishment, self-improvement, recognition of one's worth and rest for one self. The three theme clusters were associated with the existence, relatedness, and growth (ERG) of ERG areas, respectively. CONCLUSIONS: We conclude that the core components of happiness in middle-aged women are to live healthy and mind-ruled and activate hope. The nature of happiness is egocentric stability in middle-aged women. The results suggest that theme clusters might be used to develop a scale for measuring happiness in middle-aged women. This will be helpful to assess the psychosocial status of middle-aged women in Korea.